Genetic and cropping cycle effects on proximate composition and antinutrient contents of flour made from eleven Musa genotypes - Baiyeri, K.P.; Tenkouano, A. (African Journals Online, 2006)
Eleven Musa genotypes comprising ten hybrids and one local check were grown for two cropping cycles (plant crop and ratoon crop) in a sub-humid location of southeastern Nigeria. Flour was processed from unripe fruits harvested thereof. Proximate qualities and antinutrient factors were determined for each genotype during the two cropping cycles. Variance components analysis revealed significant (P<0.05) genotype (G), cropping cycle (C) and G x C interaction effects on most of the traits. The percent protein content was not influenced by any of the variance components. However, flour made from bunches harvested during the second cropping cycle (ratoon crop) had significantly (P<0.05) higher values for carbohydrate, fat, energy and tannin than the first cropping cycle (plant crop) harvest. The plantains had lower ash than the cooking and dessert bananas. Principal component analysis suggested carbohydrate, fat, moisture and level of antinutrient factors as major discriminant variables for characterizing bananas and plantains fruit flour into quality groupings. The study showed that the new Musa hybrids have comparable proximate qualities and level of antinutrient as the preferred local check ‘Agbagba'. This suggests that the new hybrids could be released for production and consumption.